Vitamin D Insufficiency Among Professional Basketball Players: A Relationship to Fracture Risk and Athletic Performance. Issue 5 (11th May 2018) - Grieshober, Jason A.; Mehran, Nima; Photopolous, Christos; Fishman, Matthew; Lombardo, Stephen J.; Kharrazi, F. Daniel
Background: Vitamin D is believed to play a role in influencing fracture risk and athletic performance. Insufficiency of vitamin D affects an estimated three-quarters of the United States population. Hypovitaminosis D has also been demonstrated to be quite common among professional basketball players in the National Basketball Association (NBA). Purpose: To determine whether a relationship exists between vitamin D levels and fracture risk and athletic performance (as measured by NBA draft status) among elite basketball players. Study Design: Descriptive epidemiology study. Methods: Data were obtained from the NBA regarding combine participants from 2009 through 2013. This information included vitamin D level, demographic information, fracture history, and NBA draft status. The data were analyzed to determine associations between vitamin D level and fracture risk and NBA draft status. Results: Vitamin D levels were measured for 279 players at the NBA Combine from 2009 through 2013. Vitamin D deficiency (<20 ng/mL) was seen in 32.3% of athletes, vitamin D insufficiency (20-30 ng/mL) was seen in 41.2%, and sufficient levels of vitamin D (>30 ng/mL) were present in only 26.5%. A total of 118 players had a history of at least 1 fracture. Vitamin D level was not predictive of fracture risk. Contrary to our hypothesis, players with a history of stress fracture had a significantly greater mean vitamin D level than those without such history (30.7 vs 25.1 ng/mL; P = .04). A majority (79.6%) of participants were selected in the NBA draft. Players with deficient vitamin D levels had a significantly lower rate of being drafted into the NBA ( P = .027). The NBA draft rate was found to increase with increasing levels of vitamin D ( P = .007). Conclusion: Hypovitaminosis D is quite common among NBA Combine participants, affecting 73.5%. While no significant relationship was found between vitamin D level and fracture history, patients with a history of stress fracture had significantly greater mean vitamin D levels. Additionally, participants with greater vitamin D levels were more likely to be drafted into the NBA. This information supports the potential role of vitamin D in influencing athletic performance.